Ncf1 Governs Immune Niches in the Lung to Mediate Pulmonary Inflammation in Mice - Li, Mengyao; Zhang, Wentao; Zhang, Jing; Li, Xiaowei; Zhang, Fujun; Zhu, Wenhua; Meng, Liesu; Holmdahl, Rikard; Lu, Shemin (Frontiers in Immunology, 2021)
Neutrophil cytosolic factor 1 (Ncf1) is a major genetic factor associated with autoimmune diseases and has been identified as a key player in autoimmune mediated inflammation. We addressed the role of Ncf1 in an antigen-induced pulmonary inflammation model, and found that the Ncf1m1j mutation, causing a deficient reactive oxygen species response, alleviated disease. The Ncf1m1j mutation was associated with a reduced inflammatory cell infiltration in airways, but had limited effect on mucus secretion, antibody production and lung fibrosis. The disease remission in the Ncf1 mutated mice was reversed when functional Ncf1 was transgenically expressed in alveolar macrophages, suggesting that the cellular inflammation was depended on functional Ncf1 in alveolar macrophages. By determining cytokine and chemokine profiles in lung and serum, we found that Ncf1 deficiency allowed an increased expression of Th1 cytokines, including TNF-α, IFN-γ and IL-12. Since also epithelial cytokines were found to be regulated by Ncf1, we tested the effect of Ncf1 in IL-33 and IL-25 induced lung inflammation models. Mice with the Ncf1m1j mutation showed less sensitivity to IL-33, but not IL-25, induced lung inflammation, in a macrophage independent manner. The mice with deficient Ncf1 showed a reduced eosinophil infiltration and group 2 innate lymphoid cell (ILC2) activation. The production of IFN-γ in CD4+ T cells was increased, whereas IL-5 and IL-13 in ILC2 were decreased. Importantly, anti-IFN-γ antibody treatment of Ncf1 deficient mice increased eosinophil infiltration and rescued ILC2 activation in the lung. We conclude that Ncf1 deficiency enhances Th1 response, deactivates ILC2, and protects against pulmonitis.